La scarsa attendibilità del CAP come riferimento geografico in Italia - Ronconi, Marianna; Pasquinelli, Alice; Privitera, Anna; Guzzetti, Franco (GEOmedia, 2016)
Many software made in the USA for analyzing big territorial risks use Post Code (P.C.) as a geographical reference. However, if those software are used in Italy, the purpose of the Post Code as territorial reference results unsuitable. In fact, in Italy the P.C. was created to facilitate the processes of mail delivery. It is made up of a five numbers code and the level of information contained decreases the deeper the code is analyzed and the more their territorial continuity fails. Moreover, at times a single Post Code refers to multiple towns, at others a single town can be divided in various P.C. This article shows some examples on how the Post Code can not be used in Italy for analyze territorial distribution of natural disasters.